2013
DOI: 10.5430/jnep.v3n11p152
|View full text |Cite
|
Sign up to set email alerts
|

Coping and health in novice and experienced nursing students during clinical practice: a descriptive, differential and correlational analysis

Abstract: Aim: This study identifies the differences in novice and experienced nursing students' reports of coping and their relationship with health.Background: Clinical practice constitutes a particularly stressful training period in an academic context that activates many coping resources in students. However, there is little empirical evidence about the coping strategies used by novice and experienced nursing students during clinical practice. Both ineffective and adaptive efforts are manifested in health (physio-ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Jimenez‐Jimenez et al. () conducted a cross‐sectional study in 357 nursing students in Spain to compare self‐reported coping skills in novice and experienced nursing students. Nursing students were identified who used a self‐confident approach when faced with stress such as ‘being optimistic when dealing with stressors’ and ‘having confidence when overcoming problems’.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jimenez‐Jimenez et al. () conducted a cross‐sectional study in 357 nursing students in Spain to compare self‐reported coping skills in novice and experienced nursing students. Nursing students were identified who used a self‐confident approach when faced with stress such as ‘being optimistic when dealing with stressors’ and ‘having confidence when overcoming problems’.…”
Section: Resultsmentioning
confidence: 99%
“…; Jimenez‐Jimenez et al. ). Similarly, in two studies in Arab countries, students identified avoidance styles as their least frequently utilized ways of adapting to stressful events (Hamaideh et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) What are the senior nursing students' responses to stress in clinical practice? (3) What are the stress coping strategies used by senior nursing students?…”
Section: Research Questionsmentioning
confidence: 99%
“…[1] Although growing literature view nursing clinical practice as a stressful experience that can cause negative consequences on both students' academic performance as well as their well-being. [2][3][4][5] Stress experienced by nursing students has profound effects on educational programs, on nurse employers, and the entire nursing profession. Stress not only jeopardize students' competencies, increase nursing shortage via increasing intention to leave the profession, but also endanger the entire quality of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%